2021
DOI: 10.1246/bcsj.20210335
|View full text |Cite
|
Sign up to set email alerts
|

Maze Pattern at Nanometer-Scale in a Mixed Langmuir Monolayer of Fatty Acids

Abstract: We investigated the morphology of binary monolayers of palmitic acid and behenic acid using atomic force microscopic observations. The monolayers exhibited a phase-separated morphology composed of meandering domains with a width of nanometer order, which is probably due to fixation of the monolayer morphology at a stage on the way to phase separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It is, therefore, concluded from Figures – and previous results (C 16 /C 22 , C 16 /C 24 ) that the molecular aggregation state, such as the molecular mixing or the phase separation of the mixed monolayer, depends on the difference in the number of methylene groups in the alkyl chain of a fatty acid molecule: the mixed system with a difference of four methylene groups was in a molecular mixing state and that of six and eight methylene groups were in a phase-separated state.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…It is, therefore, concluded from Figures – and previous results (C 16 /C 22 , C 16 /C 24 ) that the molecular aggregation state, such as the molecular mixing or the phase separation of the mixed monolayer, depends on the difference in the number of methylene groups in the alkyl chain of a fatty acid molecule: the mixed system with a difference of four methylene groups was in a molecular mixing state and that of six and eight methylene groups were in a phase-separated state.…”
Section: Resultsmentioning
confidence: 62%
“…Previous morphological studies for the (C 16 /C 22 ) and (C 16 /C 24 ) mixed monolayers (Figure S1 for C 16 /C 24 ) and Figure for the (C 16 /C 20 ) mixed monolayer showed that the molecular aggregation state of the mixed monolayer of fatty acids depended on the difference in the number of methylene groups (in other words, the difference in the cohesive energy of each alkyl chain): the molecularly mixed state was observed for the difference of four methylene groups, and the phase-separated state was observed for the difference of six and eight methylene groups. Next, the monolayer morphology was investigated using the different combinations (by fixing one fatty acid to C 24 ) of fatty acids.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…4). 53 These structurally precise patterns are probably nanoarchitected through fixation of a two-dimensional morphology on the way to phase separation. Such delicate patterns would be useful in certain kinds of advanced applications such as nanoelectronics, nanophotonics, and nanosensing.…”
Section: Organic Molecules and Related Materialsmentioning
confidence: 99%